Effectiveness of Bio-organic Fertilizer Formulas to Increase Productivity of Upland Rice and Dehydrogenase Activity in Lampung Acid Upland - Surono, .; Santosa, Edi; Subowo, .; Elsanti, .; Khamdanah, . (UNIVERSITY OF LAMPUNG, 2015)
Development of acid upland in Indonesia still has constraints. To solve the constraint, environmental friendly technology by using organic matter and beneficial microbes is necessary. This study aimed to determine the effectiveness of bio-organic fertilizer formulas for increasing productivity of upland rice plant in acid upland. This study used a randomized block design with 11 treatments using un-treatment as a control and some combination of NPK and bio-organic fertilizer. Each treatment was repeated three times, the size of plot was 5 m x 5 m. Upland rice var. Situ Patenggang was used as a plant indicator, with cultivication spacing of 40 cm x 15 cm. Combination treatment of NPK and bio-organic fertilizer increased population of P-solubilizer and N-fixer bacteria, plant height and tillers. Treatments of NPK-rec, ¾ NPK-rec and combination of ½ NPK-rec, ¾ NPK-rec and NPK-rec with both bio-organic formulas gave the weight of dried unhusked upland rice equal was 1.92 to 2.56 t ha-1 significantly higher compared to the control. The highest RAE was generated by treatment of NPK-rec combined with Bio-Organic Formula II about 137%. Bio-Organic Formula II could increase the growth and productivity of upland rice var. Situ Patenggang and could increase the efficiency udeof ½ NPK fertilizer dosage recommendations or equivalent with 125 kg urea, SP-36 100 kg, and 35 kg KCl ha-1 and increased the dehydrogenase activity.